PENGARUH LKPD BERBASIS GAMBAR PROSES TERHADAP HASIL BELAJAR DAN KEMAMPUAN BERPIKIR KRTIS SISWA KELAS VIII PADA MATERI CAHAYA - Neneng Khoirunnisa; sutarto sutarto; Aris Singgih Budiarso (Saintifika, 2021)
This study aims to determine the effect of using picture-based worksheets on the material process on learning outcomes and critical thinking skills. This type of research is a quasi-experimental research with a posttest control group design. The data from the Independent Sample T-Test test obtained a sig value. (2-tailed) of 0.002 and the right-hand t-test which shows the results of the calculation tcount (3.362) > ttable (2.018) which means that there is an influence of process image-based worksheets on learning outcomes. Meanwhile, to test the ability to think critically using the Mann Whitney U-Test test which obtained the Asymp value. Sig. (2-tailed) of 0.014, which means the significance value is <0.05, which means that H0 is rejected and Ha is accepted. So there is an influence of process image-based worksheets on critical thinking skills. Based on the results of the study, it can be concluded that the process image-based worksheets significantly affect student learning outcomes and critical thinking skills